BAJO TRIBE HOUSEHOLD BUSINESS MODEL IN TOROKEKU VILLAGE TINANGGEA DISTRICT KONAWE SELATAN DISTRICT - Fajriah Fajriah; Kobajashi Togo Isamu; Titin Rahmiatin (Universitas Muhammadiyah Kendari, 2019)
This research aims to know (1) the business type of people in Torokeku Village, Bajo Regency of South Wawoni Island (2) the available facilities and infrastructure in Torokeku village (3) strategies that can be done to develop household-based businesses in Torokeku village. This research used qualitative descriptive method. Subject of the research were the indigenous people of Torokeku, Bajo regency. Data collection techniques employed three techniques namely observation, interviews and documentation. The data were analyzed using Descriptive and SWOT analysis. The study found that (1) the type of business that were run by the inhabitants of Torokeku were dominated by seafood such as dried seaweed business, the selling dry and wet sea cucumber and fish fresh coral. In addition they also establish some household business such as making cake and drinks as well as grocery sales. Seen in terms of its economic, the dried sea cucumber bring more values rather than the dried seaweed; (2) several facilities and infrastructures have not met the requirements to support the household business run by the indigenous of Torokeku, in Bajo district. For example there is no any production space for processing of seafood. The selling products were only sold to regular buyer and the toilets have not been fulfilled (3) strategies that can be done to develop a household business is by promoting the Bajo neighborhood as a central processing of seaweed and sea cucumber to the public, arrange the environment and create a kiosk or sellers as well as seafood processing in order to be a sales center by traditional Tribal villages of origin Torokeku Bajo.